Taking the Law into their (Virtual) Hands: Facebook and Digital Vigilantism - Cox, Christine Anne R (Archīum Ateneo, 2024)
Digital vigilantism is an emerging phenomenon whereby netizens engage in forms of targeted surveillance, naming and shaming through new media, supposedly for social justice ends. The multi-layered case of Christine Dacera, the Filipina flight attendant who was found dead on New Years Day 2021, is one such case that warrants the critical investigation of the role of Facebook in vigilant behaviors of Filipino users. Using netnographic data and an affordances approach, this study asks the following: What are the dominant affordances associated with the use of Facebook for digital vigilantism, and how does surveillance enable the new normal of community policing and punishing of perceived transgressions of human rights? The analyses unearthed the ways that clicks, reacts, likes, and shares can translate into weaponized data and politically exploitable information. It showed how information can be abundant but at the same time carefully (and sometimes maliciously) crafted and amplified through legacy media. It appears that the networked interactions afforded by Facebook allows for the quick, ad hoc formation of affective publics rallying for a cause, but it does not necessarily sustain a productive union of people, ideas and tangible actions demanded by vigilant behavior. Facebook's features can aid hashtag protests such as #JusticeForChristineDacera by reducing the costs of information transmission, constructing a collective identity and maintaining weak ties. The digital platform affords users to speak to like-minded participants and have constant access to materials circulating within their networks, but may also result in the formation of online echo chambers and discourses rooted in misinformation.